Vigilância da infecção pelo Mycobacterium leprae por meio de sistema de informação geográfica e de ferramentas moleculares e imunológicas em município de alta endemia de hanseníase no estado de Minas Gerais - Nicchio, Mariana Vitorino Candeiro (2016)
Leprosy is a public health problem in developing and low income countries. Household contacts of leprosy patients (HHCs) are at risk for the development of disease and may be involved in Mycobacterium leprae chain of transmission. To characterize the leprosy endemic of the municipality of Ituiutaba in the period from 2004 to 2014, using georeferencing tools, from new cases reported not SINAN in this period and carry out molecular epidemiology among leprosy contacts. Geographic Information Systems (GIS) and spatial analysis are efficient tools to determine regions of risk and support early detection of new cases. Applied GIS to explore the distribution of leprosy cases (N=303), reported during 2004 to 2014, and of HHCs (N=53), in a highly endemic area of southeast Brazil, were analyzed according to leprosy classification of the cases and the subclinical infection determined by serology among HHCs, to evaluate risk for disease onset and transmission, as well support prevention strategies. In the analyzed period 57.4% (213/371) of patients had multibacillary and 42.6% (158/371) were considered paucibacillary cases. for genres, most of the cases were female, with 52.6% (195/371) of cases (p <0.05). As for the age group, more than half of the cases 47.7% (177/371) was between 35 and 59 years, with a statistically significant difference from the other (p <0.05) for the clinical classification of new cases (classification Madrid ), the manifestation borderline was the most prevalent, comprising 47.2% (175/371) of patients in this study. While the detection of <15 years left the hyperendemic parameter, with 18.54 cases per 100,000 hab. for reaching the low parameter.. Positivity among the HHCs with subclinical infection: 17% for anti-PGL-I ELISA and 42% for anti-LID-NDO rapid lateral-flow test. The detection of cases showed a 43% decline in 10 years of the study (P <0.05), remaining in highly endemic detection parameter (20 to 39.99 cases / 100,000hab.) Seventy percent (38/60) was observed among contacts of index cases manifesting multibacillary (MB) leprosy. Spatial distribution of leprosy cases was highly heterogeneous throughout the urban perimeter. Four main clusters of patients and three main clusters of subclinical infection were identified. Spatio-temporal epidemiology associated to serologic analysis can increase the effectiveness of the control strategies through the identification of areas of disease burden and of M. leprae transmission, providing critical information to support the action planning of health interventions in regions of interest.